Artikel Review : Penyebab Cacat pada Sediaan Kemasan Obat di Perusahaan Farmasi - Nabila Sativa; Nailia Nur Isma Sumarno; Nor Latifah (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Pharmaceutical packaging serves not only as a means of protecting the product but also as a source of information and quality assurance for consumers. However, various studies indicate that packaging defects remain a significant issue in the pharmaceutical industry. This article is a literature review that examines several studies related to the analysis of the causes of packaging defects in pharmaceutical preparations. Based on the review of multiple scientific journals, it was found that packaging defects are generally caused by a combination of technical and non-technical factors, such as machine failure, operator error, inappropriate raw material specifications, and insufficient quality control.